Analysis of STP Marketing Strategy Implementation (Segmenting, Targeting, Positioning) and PLC (Product Life Cycle) at UMKM Souvenir Center : Case study on MSME Taman Sari Madiun City - Nasihiyah Purwaning Wulan; Citra Dwi Marlia Rhochayati; Sudarmiatin; Trisetia Wijijayanti (PT Maju Malaqbi Makkarana, 2026)
This study aims to analyze the implementation of STP (Segmenting, Targeting, Positioning) marketing strategies and product life cycle (PLC) in MSMEs of the Taman Sari Souvenir Center in Madiun City. The research approach used is qualitative descriptive with data collection techniques through observation, interviews, and documentation. The results of the study show that the segmentation strategy is carried out based on the demographic and psychographic characteristics of consumers, especially tourists and local people with an interest in regional products. Targeting is focused on middle to upper consumers who prioritize product quality and authenticity, while positioning is built through the image of a trusted souvenir center with superior quality and competitive prices. In PLC analysis, superior products such as Madiun cakes and traditional processed foods are currently at the maturity stage, characterized by stable sales and increasing market competition. To maintain its market position, Taman Sari MSMEs implement product innovation, attractive packaging, and digital promotion strategies through social media. These findings affirm the importance of integration between STP and PLC strategies in maintaining the competitiveness and sustainability of MSME businesses in the digital era.